Synthesis and Biological Evaluation of Some Novel 1,8-Naphthyridine Derivatives - Sraa Abu-Melha (Acta Chimica Slovenica, 2017)
A series of substituted 1,8-naphthyridine derivatives was synthesized to be used as cytotoxic and antioxidant agents by applying 1,4-dihydro-4-oxo-1,8-naphthyridine-3-carbohydrazide (1) as the starting material. Compound 1 was reacted with different reagents to afford the corresponding 3-heterarylcarbonyl-1,8-naphthyridine derivatives 3–19 which were tested for their in vitro cytotoxicity against Ehrlich Ascites Carcinoma, and antioxidant activity. Compound 15 showed the best cytotoxicity and antioxidant activity.